Vγ2 x PD-L1, a Bispecific Antibody Targeting Both the Vγ2 TCR and PD-L1, Improves the Anti-Tumor Response of Vγ2Vδ2 T Cell - Yang, Rui; He, Qing; Zhou, Hui; Gong, Cheng; Wang, Xing; Song, Xingpan; Luo, Fang; Lei, Yang; Ni, Qian; Wang, Zili; Xu, Shasha; Xue, Yan; et al. (Frontiers in Immunology, 2022)
The potent cytotoxic property of Vγ2Vδ2 T cells makes them attractive for adoptive T cell transfer therapy. The transfusing of the expanded Vγ2Vδ2 T cells into cancer patients shows well-tolerated, but the clinical response rates are required to be improved, implying that there is still an unmet efficacy with low toxicity for this novel anti-tumor therapy. In this study, we test the anti-tumor efficacy of a Y-body-based bispecific antibody (bsAb) Vγ2 x PD-L1 that preferentially redirects Vγ2Vδ2 T cells to combat PD-L1 positive tumor cells. With nanomolar affinity levels to Vγ2Vδ2 T cells and PD-L1+ tumor cells, Vγ2 x PD-L1 bridges a Vγ2Vδ2 T cell with a SKOV3 tumor cell to form a cell-to-cell conjugation. In a PD-L1-dependent manner, the bsAb elicits effective activation (CD25+CD69+), IFNγ releasing, degranulation (CD107a+), and cytokine production (IFNγ+ and TNFα+) of expanded Vγ2Vδ2 T cells. The activations of the Vγ2Vδ2 T cells eliminate PD-L1-expressing human cancer cell lines, including H1975, SKOV3, A375, H1299, and H2228 cells, but not PD-L1 negative cells including HEK-293 (293) cells and healthy PBMCs. Finally, we show that combining Vγ2 x PD-L1 with adoptively transferring Vγ2Vδ2 T cells inhibits the growth of existing tumor xenografts and increases the number of Vγ2Vδ2 T cells into the tumor bed. Vγ2 x PD-L1 represents a promising reagent for increasing the efficacy of adoptively transferred Vγ2Vδ2 T cells in the treatment of PD-L1 positive malignant tumors.